2014
DOI: 10.1007/s40204-014-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characteristics of gamma-irradiated gelatin

Abstract: This article reports the effects of gamma irradiation (dose ranges 0.1–10 kGy from 60Co source) on the characteristics of solid gelatin and the physico-mechanical, microstructural and bioactive properties of the scaffold prepared from irradiated gelatin solution. FTIR, intrinsic viscosity, bloom strength, thermal properties, SEM, tensile properties, water uptake ability and antimicrobial activities of non-irradiated and irradiated solid gelatin and its scaffolds were investigated. The detailed experimental res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The water uptake capacity of both nonirradiated and γ-irradiated HGCs (appeared as HGC shells deformation and swelling) could explain the results obtained for the onset of MB solution leakage, which agree with previous findings 18 , showing lower water uptake for γ-irradiated HGCs than for nonirradiated HGCs up to 2.5 kGy. The authors suggested that radiation doses up to 2.5 kGy induced crosslinking along with interconnection among the gelatin pores due to the formation of a three-dimensional network as a function polypeptide chain crosslinking.…”
Section: Figure 1 Ftir Spectra Of (A) Non-irradiated Hgcs (F1) and Hsupporting
confidence: 91%
See 3 more Smart Citations
“…The water uptake capacity of both nonirradiated and γ-irradiated HGCs (appeared as HGC shells deformation and swelling) could explain the results obtained for the onset of MB solution leakage, which agree with previous findings 18 , showing lower water uptake for γ-irradiated HGCs than for nonirradiated HGCs up to 2.5 kGy. The authors suggested that radiation doses up to 2.5 kGy induced crosslinking along with interconnection among the gelatin pores due to the formation of a three-dimensional network as a function polypeptide chain crosslinking.…”
Section: Figure 1 Ftir Spectra Of (A) Non-irradiated Hgcs (F1) and Hsupporting
confidence: 91%
“…The authors showed that all hydrogels collapsed as the NaCl concentration increased. The slower in-vitro rupture time of F2 and F3 γ-irradiated HGCs thanF1 non-irradiated HGCs in deionized water (Figure 3) is attributable to the polypeptide chain crosslinking induced by the γ-radiation, which inhibited the water from entering the HGCs 18 . However, at radiation doses >3 kGy, faster invitro rupture times (disintegration/dissolution) were observed as a result of the degradation effect of γ-radiation doses >3 kGy.…”
Section: Effects Of Dissolution Medium and γ-Radiation Dose On Hgc Inmentioning
confidence: 99%
See 2 more Smart Citations
“…The fish gelatine composite membranes with different amounts of bLF were evaluated with respect to antibacterial efficiency against E. coli and S. aureus, for 120 minutes. As shown in figure 5, the electrospun fish gelatine mats by itself displayed a considerable bacterial reduction when compared with the inoculum of 2-log, which is probably attributed to the nature of gelatin and was previously observed against E. coli [56]. This may be due to the swelling nature of the electrospun mats that do not provide the adequate conditions for bacteria cellular growth.…”
Section: Resultsmentioning
confidence: 76%